The Effect of CEO Foreign Experience on Climate Change Disclosure with Executive Compensation as a Moderating Variable - Iskandar Itan; Sukiantono Tang; Sheila Septiany; Kennardi Tanujaya; Yanti Yanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines the relationship between CEO foreign experience and climate change disclosure among Indonesian listed companies, using the Task Force on Climate-Related Financial Disclosures framework. Drawing on Upper Echelons Theory, the study explores how executive background and governance mechanisms shape corporate transparency in response to climate-related risks. Using panel data from 1,925 firm-year observations of companies listed on the Indonesia Stock Exchange from 2020 to 2023, the analysis employs ordinary least squares regression as the main estimation method, while generalized least squares is used as a robustness check to ensure the consistency of the results. The findings reveal that a CEO’s foreign experience is negatively associated with climate change disclosure, suggesting that firms led by CEOs with overseas experience tend to disclose less climate-related information. In contrast, executive compensation has a positive effect on disclosure. Further analysis reveals that executive compensation negatively moderates the relationship between CEO foreign experience and climate change disclosure, suggesting that incentive mechanisms weaken the disclosure behavior of foreign-experienced CEOs. This study contributes to the literature by providing new evidence on how leadership characteristics and compensation structures shape corporate climate transparency in an emerging market context.